Réponses

2012-11-14T06:40:37+01:00

(2x+3)-(9x+1)=0

2x+3-9x-1=0

-7x+2=0

-7x=-2

x=2/7

 

6x+3=x+13

6x-x=13-3

5x=10

x=10/5=2

 

(2x+3)(9x+1)=0

18x²+2x+27x+3=0

18x²+29x+3=0

 

delta=b²-4ac=29²-4*18*3=841-216=625

2 solutions

la premiere =(-b-Racine ² delta)/2a=(-29-25)/36=-54/36

la seconde =(-29+25)/36=-4/36=-1/9

2012-11-14T07:46:51+01:00

2x + 3) - (9x + 1) = 0

2x + 3 -9x -1 = 0

-7x + 2 =0

-7x = -2 

x= -2/7

 

6x + 3 =x + 13

6x - x = 13 - 3

5x = 10

x = 10/5

x = 2

 

(2x + 3 ) ( 9x + 1) = 0

équation produit nul l'un des deux est = 0

donc (2x + 3) =0  donc 2x = -3 x = -3/2

soit (9x + 1) =0 donc 9x = -1 x = -1/9